Binary lanthanide(iii)/nitrate and ternary lanthanide(iii)/nitrate/chloride complexes in an ionic liquid containing water: optical absorption and luminescence studies. Issue 6 (14th February 2015) - Ansari, Seraj A.; Liu, Lisheng; Rao, Linfeng
<x xml:space="preserve">Abstract</x> Thermodynamic and spectroscopic data indicate that nitrate and chloride are stronger ligands than water for lanthanides in water saturated BumimTf2N.